Role of Artificial Intelligence in different aspects of Public Health - Ifra Chaudhary; Hassan Anwar; Umar Latif; Ali Latif (UMT Artificial Intelligence Review, 2022)
In the next decade of disease surveillance research, innovative and novel techniques are required to utilise massive quantities of complex and multi-dimensional data, effectively. Public health is one of the most significant domains of public governance and artificial intelligence has emerged as an innovative problem-solving technique in this domain. Artificial intelligence is a requirement for the early identification of diseases and disasters in order to prevent high mortality rates and reduce economic burden by timely providing appropriate healthcare. This detection is made possible in this research by identifying patterns in the database. This review shows that the use and development of AI techniques has increased in the field of public health over the past few years and most of the existing studies show a positive impact of AI in the domain of public health. This study is divided into three portions. The first portion reviews the role and potential usage of artificial intelligence in epidemics, since it is very important to timely investigate them and AI has the potential to cope with them. The second part of the review provides a detailed discussion about serious game usage in public health. Serious games are used for the training and rehabilitation of the gamer. The third part deals with the management of public health emergencies including evacuation, causality response, and information processing.